Nanoscale distribution of Pb in monazite revealed by atom probe microscopy - Fougerouse, Denis; Reddy, Steven; Saxey, David; Erickson, Timmons; Kirkland, Chris; Rickard, William; Seydoux-Guillaume, A.; Clark, Christopher; Buick, I. (Elsevier Science BV, 2018)
© 2018 Elsevier B.V. The widespread use of monazite (LREEPO 4 ) in U-Pb geochronology is underpinned by the assumption that it incorporates negligible amounts of Pb during initial growth, and that radiogenic Pb remains immobile after formation. We have investigated the nanoscale distribution of Pb in monazite from granulite facies rocks of the Sandmata Metamorphic Complex (Rajasthan, India) by atom probe microscopy to further understand the utility of monazite as a geochronometer. The studied monazite contains distinct 10 nm clusters, enriched in Ca and with a bulk composition consistent with them being apatite (Ca 5 (PO 4 ) 3 (OH)), that are also enriched in Si and Pb relative to the monazite host. The 208 Pb/ 232 Th ratios of the clusters ranged from 1.1 ± 0.1 to 1.4 ± 0.2 (2s), indicating that the clusters hold unsupported Pb. The 208 Pb/ 232 Th ratios of the whole specimen (including clusters) and the matrix alone are similar ( < 6% difference), indicating that the clusters formed shortly after monazite crystallisation by a phase exsolution mechanism that partitioned the initial common Pb and the minor radiogenic Pb into apatite. A volume-dependent analysis of the bulk monazite composition shows that a large variability in the Ca and, by proxy, Pb composition at small volumes (125 to 10,000 nm 3 ) due to its heterogeneous distribution in the clusters, may have detrimental effects on radiometric dating with small analytical volumes. At larger volumes, including those used in EPMA and traditional isotopic dating methods (LA-ICPMS, SIMS), the variability of Pb content is negligible. However, the measured composition may result from the mixing of multiple reservoirs.